Determination of melamine in milk and dairy products by microchip-based high-field asymmetric ion mobility spectrometry combined with solid-phase extraction. (1st December 2015) - Zhao, Wei-jun; Wang, Yonghuan; Li, Juan; Li, Ling-feng; Wang, Qi; Han, Ke; Zhang, Yuang; Li, Xin; Li, Peng; Luo, Jikui; Wang, Xiaozhi
Highlights: As a detector, standalone FAIMS can directly analysis of melamine. The determination time was very short and was not use of any organic solvents for FAIMS. This technology was an atmospheric pressure gas phase ion quantification. This new method provides a huge potential application value for rapid analytical fields. Abstract: This article presents a method for sensitive, fast and quantitative determination of melamine in milk and dairy products using high-field asymmetric ion mobility spectrometry (FAIMS). The solid-phase extraction (SPE) technology was used for purification after the sample was extracted by organic solvents, and followed by the analysis of FAIMS. The measurement parameters and variables that affect the FAIMS detection have been investigated, and optimum conditions have been obtained as follows: the carrier gas flow rate is 1.6 L min −1, the headspace sampler temperature is 150 °C, the pressure is 1 atm, and the humidity is 2.0 g m −3 . The results showed that the SPE–FAIMS method can detect melamine in samples with a concentration down to 0.1 mg kg −1 . The ion intensity has a linear relationship with melamine concentration in the range from 0.3 mg L −1 to 25 mg L −1, with a good linearity of 0.9975. The limits of detection (LOD) and limits of quantification (LOQ) are 0.1 mg kg −1 and 0.3 mg kg −1 in milk and dairy products, respectively, and the relative standard deviation is less than 8.0%. The results demonstrated that FAIMS has great potential as a powerful tool for food analysis and safety inspection.